Welfare Dynamics with Synthetic Panels The Case of the Arab World in Transition - Dang, Hai-Anh H. (World Bank E-Library Archive, 2016)
This paper studies welfare dynamics, especially changes associated with middle-class status in countries in the Middle East and North Africa, before and after the Arab Spring transitions, using objective and subjective welfare measures. Absent panel data, the analysis employs state-of-the-art synthetic panel techniques using repeated cross sections of expenditure data from household surveys and subjective well-being data from value surveys, which were conducted during the 2000s and the Arab Spring period. The objective welfare dynamics indicate mixed trends. About half the poor in the 2000s moved out of poverty by the end of the decade, but chronic poverty remained high; upward mobility was strong in Syria and Tunisia, but downward mobility was pronounced in Yemen and Egypt. Subjective well-being dynamics suggest negative evelopments in most countries during the Arab Spring transitions. Low education achievement, informal worker status, and rural residency are positively associated with lower than average chances for upward mobility, and greater than average chances for downward mobility according to both types of welfare measures